Effect of a natural fermentation liquid supplement on health performance carcass characteristics and rumen fermentation dynamics in beef feedlot cattle - Erasmus, L.J. (Lourens Jacobus) (University of Pretoria, 2015)
Dissertation (MScAgric)--University of Pretoria, 2015.